Lessons from computer simulations of Ras proteins in solution and in membrane - Prakash, Priyanka; Gorfe, Alemayehu A. (Biochimica et biophysica acta, 2013)
A great deal has been learned over the last several decades about the function of Ras proteins in solution and membrane environments. While much of this knowledge has been derived from a plethora of experimental techniques, computer simulations have also played a substantial role. Our goal here is to summarize the contribution of molecular simulations to our current understanding of normal and aberrant Ras function. We focus on lessons from molecular dynamics simulations in aqueous and membrane environments. The central message is that a close interaction between theory and simulation on the one hand and cell-biological, spectroscopic and other experimental approaches on the other has played, and will likely continue to play, a vital role in Ras research. Atomistic insights emerging from detailed simulations of Ras in solution and in bilayers may be the key to unlock the secret that to date prevented development of selective anti-Ras inhibitors for cancer therapy. •Contribution of molecular simulations to the study of Ras GTPases•Multi-scale molecular dynamics simulations of Ras in solution and in membrane•Dynamics plays an important role in the biological activity of Ras proteins.•Implications of simulations and protein motion for anti-cancer Ras inhibitors